Seed Priming Improves Seedling Vigor and Yield of few Vegetable Crops - Maiti, R. K.; Vidyasagar, P.; Rajkumar, D.; Ramaswamy, A.; Gonzalez Rodriguez, Humberto (International Journal of Bio-resource and Stress Management, 2023)
Seed priming is a useful technique for enhancing seed vigor, and thereby, improving overall germination and seedling development in crop species. In tomato variety Gem, germination percentage, early flowering, plant height and leaf length were increased in response to hydro-priming-2 treatment. In okra and onion, seedling vigor was increased in osmo-priming. In case of watermelon, halo-priming and osmo-priming increased seedling vigor. In case of chilli, halo-priming increased seedling vigor. With respect to sponge gourd, osmo-priming increased seedling vigor. In case of ridge gourd, halo-priming increased seedling vigor. In general it is observed that the yield is increased in case tomato, chilli, and okra apart from seedling vigor. Most of the cop’s primed seeds have longevity up to 3 months from the dated of priming. The results suggest that primed seeds can be store up to 3 months only after which germination percentage decreases sharply. As the longevity of primed seeds is short, the priming technique may be used in increasing seed production of foundation seeds and breeders seeds. In addition, seed priming could improve seedling vigor in seedling nursery.